Ministry of the Interior Decree No. 1105 of the Year 2023 Amending Certain Provisions of Ministerial Decree No. 31 of the Year 1960, Concerning Visa - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic